Energy harvesting from pressured water flow with IoT monitoring - Wahid, Herman; Zolkipli, Muhammad Faris Al Hafiz; Zamri, Muhammad Zulhafiz; Razali, Halimatus Saadiah (Penerbit UTHM, 2020)
Energy harvesting are required in order to improve the green technology. Energy harvesting or also known as power harvesting is the process where the energy is gain from the outside source for example solar energy, heat energy, wind energy and kinetic energy. This energy can be collected and converted to a useful electrical energy. Harvested energy give a small amount of power for a low energy electronics. This is because the energy converted comes from the recycle of waste energy, example, heat energy that produced from the operation of engine.